AKAD-AKAD MUAMALAH DALAM FIQH: SATU ANALISIS - Ahmad Sarkawi, Azila (Jurnal Syariah, 2019)
The writer elaborates the various concepts of 'aqd according to the Islamic Law of Contracts and analyses their theoritical aspects further.